An Unusual case of Ewing’s Sarcoma of Cervical Spine - Adil Aziz Khan, Adil Aziz Khan; Sehrish Nadeem, Sehrish Nadeem; Iqra Kanwal, Iqra Kanwal; Sameer Raja, Sameer Raja (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Ewing’s Sarcoma (EWS), is a member of the Ewing sarcoma family of tumours (ESFT); a group of small round blue cell neoplasms. It arises frequently from long bones but its origin from non-sacral spine is to a great degree uncommon, representing only 0.9% of all the cases with amazingly rare association of cervical spine.1,2 Its peak incidence is in the second decade of life with slight male predominance.2 Local pain, the most common symptom, is followed by a palpable swelling. Neurological deficit produced by spinal cord compression is often a delayed presentation.1 Adequate multimodality treatment, comprising of surgery, chemotherapy and radiotherapy, is aimed for cure rather than palliation whenever possible.3 To date, the number of reported cases of EWS with primary localization in lumbar and cervical segments of the spine remains small, with cervical spine being reported extremely rarely. This is also one of the reasons why there are still several concerns about the optimal treatment.4,5 We report this rare lesion in a 16 years old male who presented with a progressively increasing posterior cervical swelling, local pain and dysphagia to solids.